IMPROVED ENERGY BUDGETING PROCESS USING MEASUREMENT AND VERIFICATION PRINCIPLES - van Aarde, Chantelle; Gous, Andries; Kleingeld, Marius (The South African Journal of Industrial Engineering, 2020)
Budgets are used to predict and measure a mine’s performance. Problems arise when the budget is developed by financial resources with little focus on operational changes. The implementation of energy-saving measures, and the number of workdays or time-of-use profiles are often neglected, making the budget obsolete. Measurement and verification principles are known for their effectiveness when addressing operational changes. This paper presents a novel approach in which measurement and verification principles are altered into financial principles by developing analogies between the fields. A critical analysis of South African mines’ budgets was conducted to create these analogies. The result of the analysis highlights the need for integration, and provides a relationship between well-established measurement and verification principles as an alternative solution to budgeting. The solution was applied to a gold mine complex in South Africa. The new budget could account for an additional R26.2-million (16.8%), compared with the original budget, by successfully incorporating the measurement and verification principles.